2015
DOI: 10.1007/s11418-015-0915-7
|View full text |Cite
|
Sign up to set email alerts
|

PTEN over-expression by resveratrol in acute lymphoblastic leukemia cells along with suppression of AKT/PKB and ERK1/2 in genotoxic stress

Abstract: The bioactive components of dietary phytochemicals are in the spotlight of research institutes, due to their significant antioxidant activities and health-promoting properties. Resveratrol is a polyphenol which is found abundantly in grapes and berries and has long been known as a chemo-preventive agent. The main purpose of this study was to provide a new mechanistic insight into the growth inhibition of acute lymphoblastic leukemia cells by resveratrol along with a DNA damage agent. It was found that the trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 36 publications
1
15
0
Order By: Relevance
“…Here we show that RSV reduces proliferation and cell viability in Ramos cells ( Figure 1 ), concomitant with the induction of caspase-3 and PARP fragmentation ( Figure 2 ), which are normally associate with apoptotic cell death. These results are consistent with previous studies demonstrating that RSV promotes cell growth inhibition in NALM-6 cells [ 36 ]; induces cytotoxicity in human Burkitt’s lymphoma, Raji, and Daudi cell lines [ 40 ]; and also induces cell-cycle arrest in germinal center-like LY1 and LY18 human diffuse large B-cell lymphomas (DLBCLs) [ 15 , 17 ]. Also, in mantle cell lymphomas (MCL), specifically in jeko-1 cell line, resveratrol induces apoptosis modulating several key molecules involve in cell cycle and apoptosis [ 41 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Here we show that RSV reduces proliferation and cell viability in Ramos cells ( Figure 1 ), concomitant with the induction of caspase-3 and PARP fragmentation ( Figure 2 ), which are normally associate with apoptotic cell death. These results are consistent with previous studies demonstrating that RSV promotes cell growth inhibition in NALM-6 cells [ 36 ]; induces cytotoxicity in human Burkitt’s lymphoma, Raji, and Daudi cell lines [ 40 ]; and also induces cell-cycle arrest in germinal center-like LY1 and LY18 human diffuse large B-cell lymphomas (DLBCLs) [ 15 , 17 ]. Also, in mantle cell lymphomas (MCL), specifically in jeko-1 cell line, resveratrol induces apoptosis modulating several key molecules involve in cell cycle and apoptosis [ 41 ].…”
Section: Discussionsupporting
confidence: 92%
“…In the case of lymphomas, Jazirehi et al, reported that RSV downregulates two anti-apoptotic proteins, Bcl-XL and Mcl-1, whereas it upregulates the pro-apoptotic proteins Bax and Apaf-1 in the Burkitt’s lymphoma cell line Ramos [ 35 ]. RSV also promotes cell growth inhibition in NALM-6 cells [ 36 ] and blunts PI-3K signaling and glucose metabolism in germinal center-like LY1 and LY18 human diffuse large B-cell lymphomas (DLBCLs) [ 17 ]. However, the molecular mechanisms of action of RSV in lymphoma cells remain largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…In a model of ALL, RSV affects the post-translational modifications of p53. RSV increases p53 phosphorylation at serine15 residue and hyper-activates Phosphatase and tensin homolog (PTEN), a tumor suppressor that negatively regulates the protein kinase B (Akt/PKB) signaling pathways [ 75 ].…”
Section: Molecular Targets During Apoptosis Onset In Leukemiasmentioning
confidence: 99%
“… 20 , 21 Up-regulation of PTEN is capable to inhibit AKT activation by degradation of PI3P to PIP2 16 , 21 and facilitates the p38 MAPK signaling pathway. 22 , 23 Decreasing PTEN activity through phosphorylation of PTEN 24 or deleting of one copy of its gene increases resistance to apoptotic cell death. 25 Hence, down-regulation of PTEN may lead to a neuroprotective effect in the neurodegenerative disorders with a beneficiary role in I/R injury.…”
Section: Introductionmentioning
confidence: 99%